Increasing Student Solidarity with Traditional Game Media, Playing Methods in Lower Classes - Wahyuni, Nur (Edumaniora : Jurnal Pendidikan dan Humaniora, 2022)
This study aims to investigate methods for enhancing student solidarity through the utilization of traditional games. Employing an action research approach, the study follows the Kemmis and Taggart model, comprising four stages: planning, action, observation, and reflection, conducted across two cycles. Data collection methods include field notes, interviews, documentation, and observation, with a sample comprising 20 children aged 6-7 years. Findings indicate a notable improvement in children's solidarity levels following engagement with traditional games. Prior to participation, students in the lower class exhibited low levels of solidarity, which increased to a high category after engaging in traditional games. Furthermore, the study highlights a significant positive correlation between traditional games and enhanced student solidarity, suggesting that traditional games, when integrated into teaching practices, effectively foster solidarity among students.